2013
DOI: 10.1080/15226514.2012.735288
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Native SpeciesArrhenatherum Elatius(Poaceae) andSonchus Transcaspicus(Asteraceae) Exposed to a Heavy Metal-Polluted Field: Plant Metal Concentration, Phytotoxicity, and Detoxification Responses

Abstract: The application of vegetation cover for the phytomanagement of heavy metal-polluted soils needs prior investigation on the suitability of plant species. In this study, behaviors of Arrhenatherum elatius and Sonchus transcaspicus, two native perennial grasses that currently grow in a mine tailing, were investigated through plant metal concentration, phytotoxicity and their detoxification responses. Both of the species accumulated Ni, Cu, Cd, Co, Mn, Pb, Cr, and Zn in shoots far below criterion concentration as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Furthermore, there is no clear evidence that plants with high levels of BAF have high TFs and vice versa. However, in the presented results, the metals showed high values of BAF in the roots and lower in the aerial parts, which is consistent with some previous research (Lu et al, 2013;Nikolic and Svetovic, 2015;Singh et al, 2017).…”
Section: Metal Accumulation and Distribution In Plantssupporting
confidence: 93%
“…Furthermore, there is no clear evidence that plants with high levels of BAF have high TFs and vice versa. However, in the presented results, the metals showed high values of BAF in the roots and lower in the aerial parts, which is consistent with some previous research (Lu et al, 2013;Nikolic and Svetovic, 2015;Singh et al, 2017).…”
Section: Metal Accumulation and Distribution In Plantssupporting
confidence: 93%
“…Furthermore, in S. transcaspicus activity of SOD, POD, CAT, and APX in the shoots and roots was high. Activity of all these enzymes in the roots of A. elatius was also high, but in the shoots only POD activity was high (Lu et al, 2013). Nadgorska-Socha et al (2013) found that in Cardaminopsis arenosa and Plantago lanceolata growing in mining areas, activity of SOD, POD, and GSH increased whereas nonprotein-SH group content and proline decreased as a response to metal exposure.…”
Section: Plant Physiological Adaptation On Mine Wastementioning
confidence: 98%
“…Despite high oxidative stress, this species is capable to promote biosynthesis of soluble and cell-wall phenolics and other free radical scavenging compounds as a response to metal(loid)s stress on mine spoil (Randjelović et al, 2016). Lu et al (2013) showed that Sonchus transcaspicus had a higher adaptive potential to metal-induced oxidative stress compared to Arrhenatherum elatium growing on mine tailings. Photosynthetic efficiency (Fv/Fm) and chlorophyll content decreased in both plants, but it is more pronounced in A. elatius.…”
Section: Plant Physiological Adaptation On Mine Wastementioning
confidence: 99%
“…Numerous plant species are already known to be able to remediate soils contaminated with heavy metals. They are part of families such as: Brassicaceae [54][55][56], Asteraceae [57][58][59][60], Chenopodiaceae [61][62][63], and Scrophulariaceae [64,65].…”
Section: Discussionmentioning
confidence: 99%